TANGO paper building blocks and code-base - Jeff Guo (15498743) (2025)
This data share contains: All enforced building block subsets used in the TANGO paper The general building block stock (frag-reac-zinc-stock) The code-base used to run the experiments in the paper. It is an archived state of the public saturn repository and can also be found here: https://github.com/schwallergroup/saturn/tree/de5cd7f9b61f98b1fc557b4d0d1c10c9a9be810d